FUNGSI KESENIAN TRADISIONAL KUDA LUMPING DI DESA SINAR TEBUDAK KECAMATAN TUJUH BELAS KABUPATEN BENGKAYANG - Marselius, Marselius; Istiandini, Winda; Istiandini, Winda; Muniir, Asfar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research to describe the function of traditional arts of Kuda Lumping in Sinar Tebudak village. The problem of this research were how the function of traditional Art of Kuda Lumping in Sinar Tebudak village. How to designe the implementation of research results the function of traditional Art of Kuda Lumping in Sinar Tebudak village.The method used in this research was descriptive method, with qualitative form and uses an anthropological approach. The source of data in this research was Suparmin, Paimun, and Bohiran. The data in this research were the results of interfiws and observations in the form of sound recordings, photographs and videos. The data collection techniques in this research were the form of observation, interview, and documentation techniques. Validity check of data in the form of extention of observation and triangulation. The data analysis techniques use interactive data analysis, wich is divided into four stages, including data collection, data reduction, data presentation, and power verification.The results of this research were entertainment functions, ritual functions, comunication functions, economic functions and  the results of this research were expected to be implemented in dance learing for cultural arts subjects and skills, junior high school class VIII semester one. Keywords: Java community in Bengkayang regency, Kuda Lumping, The function of traditional art.